Karya Musik Eksperimental "Wind Chimes" - Mahayasa, I Pande Komang Bintang; Garwa, I Ketut; Hartini, Ni Putu (GHURNITA: Jurnal Seni Karawitan, 2025)
Wind chimes in the form of tubes hung on the veranda, made of tubes or rods with diameters, and when they collide with each other can produce sound. In general, all types of wind chimes are musical instruments that produce beautiful sounds due to the vibrations of the tubes that are hit when the wind blows. Each bell or rod produces different tones based on the diameter, length, and thickness of the material. Based on this uniqueness, the strong desire to make wind chimes a medium of expression. Wind chimes that are developed with a larger scale than the size of wind chimes in general and have five tones that each instrument contains two octaves. "Wind Chimes" is an experimental musical art work in fulfilling the requirements for Independent Study/Project (MBKM) as the Final Assignment of the ISI Denpasar Karawitan Art Study Program. The purpose of writing this journal is to describe the stages of creation and form of the experimental musical work "Wind Chimes". The creation method used in the experimental musical work "Wind Chimes" is the Panca Sthiti Ngawi Sani method, which includes five stages: ngawirasa, ngewacak, ngarencana, ngawangun, and ngebah. This work is composed using three parts as the structure of this work. In addition, the experimental musical gamelan work "Wind Chimes" has an aesthetic value that contains postmodern aesthetics such as pastiche, camps and schizophrenia.